The Dynamics of Arrivals of Maine Migratory Breeding Birds: Results from a 24-Year Study - Wilson, W. Herbert (Biology (Basel), 2017)
This citizen-science project is the first systematic study of patterns of spring migration of Maine migratory birds. A comparison of arrival data from the Maine Ornithological Society from 1899–1911 with the modern data (1994–2017) collected for this study indicated that most species are now not arriving earlier, contrary to the predictions of earlier arrivals in the face of global warming. Arrival was synchronous across the lower two-thirds of the state for most species, although some species showed delayed arrivals along the northeastern coast compared to southern coastal areas. Only thirteen of 81 species are now arriving earlier and seven arriving later. Using quantile regression analysis with three levels of tau, the effect of year, temperature-departure from mean monthly temperature and the North Atlantic Oscillation Index were weak. Most species did not respond to any of these explanatory variables using the modern data. Leaf-gleaners showed the strongest responses. Only four species showed increasing abundance in recent years, an effect that influences detectability and hence could confound interpretation of changes in arrival date.